Abundant synthesis of long‐chain polyunsaturated fatty acids in Eutreptiella sp. (Euglenozoa) revealed by chromatographic and transcriptomic analyses. Issue 2 (9th January 2021) - Kuo, Rita C.; Zhang, Huan; Stuart, James D.; Provatas, Anthony A.; Hannick, Linda; Lin, Senjie
Abstract : Algal lipids are important molecules to store energy in algae and transfer energy in the marine food chain, and are potential materials for high value nutraceuticals (e.g., omega‐3 fatty acids) or biofuel production. However, how lipid biosynthesis is regulated is not well understood in many species including Eutreptiella from the phylum of Euglenozoa. Here, we characterized the fatty acid (FA) profile of an Eutreptiella species isolated from Long Island Sound, USA, using gas chromatography–tandem mass spectrometry (GC/MS/MS) and investigated their biosynthesis pathways by transcriptome sequencing. We discovered 24 types of FAs including a relatively high proportion of long‐chain unsaturated FAs. The abundances of C16, C18, and saturated FAs decreased when phosphate in the culture medium was depleted. Among the 24 FAs, docosahexaenoic acid (C22:6 ∆4, 7, 10, 13, 16, 19 ) was most abundant, suggesting that Eutreptiella sp. preferentially invests in the synthesis of long‐chain polyunsaturated fatty acids (LC‐PFAs). Further transcriptomic analysis revealed that Eutreptiella sp. likely synthesizes LC‐PFAs via ∆8 pathway and uses type I and II fatty acid synthases. Using RT–qPCR, we found that some of the lipid synthesis genes, such as β‐ketoacyl‐ACP reductase, fatty acid desaturase, acetyl‐CoA carboxylase, acyl carrier protein, ∆8 desaturase, and Acyl‐ACP thioesterase, were more actively expressed during light period, and two carbon fixation genes were up‐regulated in the high‐lipid illuminated cultures, suggesting a linkage between photosynthesis and lipid production. The lipid profile renders Eutreptiella sp. a nutritional prey and valuable source for nutraceuticals, and the biosynthesis pathway documented here will be useful for future research and applications.